A question of quality : state of primary education in Bangladesh - Chowdhury, A. M. Raza.; Campaign for Popular Education (Organization) (Dhaka : The University Press, 2001)
Contributed articles.
v. 1. Major findings, a synthesis
"Campaign for Popular Education"--V. 1, t.p.
Includes bibliographical references (p. [53]-55) and index.
Altab
Keywords: Education, Primary -- Bangladesh; Educational surveys -- Bangladesh; Educational evaluation -- Bangladesh; Educational tests and measurements -- Bangladesh